Новые джинсы за один вечер: украшаем, перешиваем, расписываем / [Мария Пикуль] - Пикуль Мария (Азбука рукоделия, 2007)
Экземпляры: Д.О. (20200907) / Инвентарный номер: 42129 / Цена: 124.40 / Сис.шифр: 37.24 / Авт.знак: П 32 / ГРНТИ: 64 / ББК: 37.248